How risk oversight committees reduce banking risk: the amplifying role of digital innovation - Ramdani , Deni; Yudhanto, Wildan; Aziz, Ahmad Abdul; Simamora, Alex Johanes (Institute of Computer Science (IOCS), 2025)
This study investigates the influence of risk oversight committee characteristics on banking risk. This study also investigates the moderating role of digital innovation between the influence of risk oversight committee characteristics on banking risk. Risk oversight committee effectiveness is measured by five key attributes of committee size, independence, financial expertise, risk management expertise, and meeting frequency. Banking risk is assessed across three critical dimensions which are credit risk, liquidity risk, and operational risk. Digital innovation is operationalized using the Indonesian Digital Innovation Award as a proxy for technological maturity. Samples are 27 publicly listed banks on the Indonesian Stock Exchange from 2017 to 2023. The empirical findings reveal that all risk oversight committee attributes are significantly and negatively associated with banking risk, affirming the importance of governance structures in enhancing risk resilience. Furthermore, digital innovation significantly moderates these relationships, amplifying the risk-reducing effects of each committee attributes of size, independence, financial expertise, risk management expertise, and meeting frequency. These results underscore the synergistic value of integrating governance mechanisms with digital transformation initiatives. The study contributes to the literature by bridging corporate governance and financial technology in a risk management context, and offers practical recommendations for regulators and bank executives to strengthen oversight functions in the digital era